Ag- or Cu-modified geopolymer filters for water treatment manufactured by 3D printing, direct foaming, or granulation - Tero Luukkonen (Nature Portfolio, 2020)
Abstract In this work, we compared the main characteristics of highly porous geopolymer components for water treatment applications manufactured by 3D printing, direct foaming, or granulation. Furthermore, different approaches to impregnate the materials with Ag or Cu were evaluated to obtain filters with disinfecting or catalytic properties. The results revealed that all of the investigated manufacturing methods enabled the fabrication of components that possessed mesoporosity, suitable mechanical strength, and water permeability, even though their morphologies were completely different. Total porosity and compressive strength values were 28 vol% and 16 MPa for 3D-printed, 70–79 vol% and 1 MPa for direct-foamed, and 27 vol% and 10 MPa for granule samples. Both the filter preparation and the metal impregnation method affected the amount, oxidation state, and stability of Ag and Cu in the filters. However, it was possible to prepare filters with low metal leaching between a pH of 3–7, so that the released Ag and Cu concentrations were within drinking water standards.